A fatal Chromobacterium violaceum sepsis in infant with suspected chronic granulomatous disease - Norashikin, Samsudin; Siti Hafsyah, Mohd Hariri; Zeehaida, Mohamed (2025)
Chromobacterium violaceum is a saprophytic, Gramnegative bacilli that produces a distinctive violet pigment and is often regarded as a contaminant. Although it is rarely pathogenic in humans, significant infections have been reported, disproportionately high in individuals with chronic granulomatous disease (CGD), a genetic condition characterised by the inability of neutrophils to perform adequate oxidative metabolism during phagocytosis of catalase-producing bacteria1. .